(untitled) (Scientific journal of the Fergana State University, 2026)
The article studies the theoretical and methodological foundations of the development of conflictological competence in future teachers, the practical methodological system of developing conflictological competence in future teachers, the effectiveness of developing conflictological competence in future teachers. The practical methodological system of developing conflictological competence in future teachers is also analyzed.